Is there a relationship between fetal sex and placental pathological characteristics in twin gestations? - Shayesteh Jahanfar; Kenneth Lim (BMC, 2018)
Abstract Background Placenta plays a central role in mediating growth and development of fetuses. Sex-specific placentas may complicate this role. Methods The study aimed at investigating the association between fetal sex and placental pathological findings in twin gestations using generalized estimating equation modeling. We used a large population-based clinical data born in British Columbia (BC) and linked the fetal-maternal data to hand-searched pathology reports of 1493 twin placentas from twins born in BC Women hospital. We analyzed the data using generalized estimating equations taking the cluster nature of twins into consideration. Results About 26.5% of twins were monochorionic and 73.5% were dizygotic. Most twins were male (51.3%). About 2/3 of twins were sex concordant (66.6%). Of the sex concordant twins, similar percentages were male-male (34.7%) and female-female (31.2%). Of the sex discordant twins, the male-female (33.3%) group constituted about 1/3 of the whole population. Adjusted for chorionicity, birth weight discordance ≥30% and gestational age, the odds of chorionitis (1.38, 95% CI = 1.04-1.84), anastomosis (1.63, 95% CI = 1.22-2.19), unequal sharing of placenta (1.72, 95% CI = 1.11-2.64), placental inflammation (1.30, 95% CI = 1.05-1.62) and lesions (1.83, 95% CI = 1.02-3.31) were higher in male twins compared with females. Twins of either sex from sex-discordant pairs were less likely to have placental anastomosis compared to the reference category. Males from male-male pairs had higher odds of unequal placental sharing (74% higher) and composite inflammation (52% higher) compared with the reference twins. Conclusion Our findings suggest a relationship between sex and placental pathological results.